Analysis of Efforts to Achieve Performance-Based Capitation Indicators Talang Banjar Public Health Center - Astuti, Jesika; Solida, Adila; Augina Mekarisce, Arnild; Noerjoedianto, Dwi; Wardiah, Rizalia (Rifa'Institute, 2023)
Introduction: Performance-Based Capitation Policy is an effort to ensure FKTP performance to improve satisfaction, service quality and cost efficiency. Preliminary study, the capitation payment of the Talang Banjar Public Health Center in 2022 is only 88% with the achievement of AK 64.93 per mile, RRNS 2.12%, and RPPT 0.55%. Objective: This study aims to analyze efforts to achieve KBK indicators at Talang Banjar Public Health Center based on input and process aspects. Method: This research is qualitative research with a descriptive approach with data collection using observation, document review and in-depth interviews with 15 informants who were selected by purposive sampling. Result and Discussion: The results show that the achievement of KBK Public Health Center indicators is influenced by available inputs, namely health human resources, infrastructure, funds, and methods. The process aspect shows obstacles to achieving contact number indicators, namely difficulties in Public Health Center accessibility, promotional and preventive efforts that are not optimal, as well as reporting healthy visits, non-specialist referral indicators are influenced by the behavior of patients who want to be referred and the availability of medical devices, while controlled prolanist indicators are influenced by the difficulty of routine monitoring of officers to participants. Conclusion: A thorough evaluation is needed from BPJS Kesehatan, Dinas Kesehatan and Public Health Center leaders to identify problems that arise in achieving performance indicators as an effort to ensure the quality of service to NHI participants